UPAYA MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL BERBASIS QUIZIZZ DI KELAS VII.II SMPN 5 KOTO XI TARUSAN - Nadia Amriani; Asril; Azwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to describe the implementation of Quizizz-based digital learning media to improve students' learning motivation in Pancasila Education among Class VII.II students at SMP Negeri 5 Koto XI Tarusan. The study employed Classroom Action Research (CAR) using a qualitative approach supported by quantitative data and was conducted in two cycles consisting of planning, action, observation, and reflection. Data were collected through observation, interviews, questionnaires, and documentation and analyzed descriptively. The findings revealed that the use of Quizizz effectively enhanced students' learning motivation. The observation results increased from 50.50% in the pre-cycle to 63.79% in Cycle I and 79.53% in Cycle II. Questionnaire results also improved from 60.46% to 84.08%. Furthermore, students became more active, focused, confident, and enthusiastic during the learning process. Therefore, Quizizz-based digital learning media effectively improved students' learning motivation in Pancasila Education.